Understanding Quiet Quitting Among Remote Workers: A Qualitative Phenomenological Study - Choerul Fakih; Hariri; M. Waldin Rakhmatullah; ⁠Ichsan Prastya Firmansyah (International Journal of Management and Business Economics, 2026)
The phenomenon of quiet quitting has emerged as one of the most consequential yet understudied challenges in contemporary human resource management. Although quantitative attention to the construct has grown rapidly since 2022, qualitative evidence on how remote workers themselves experience quiet quitting remains scarce. This study addresses that gap with a direct objective: to explore how remote knowledge workers interpret, enact, and rationalise quiet quitting in digitally mediated work contexts. Drawing on in-depth semi-structured interviews with fifteen remote workers spanning six industries, we employed a Gioia-methodology inductive approach to generate a grounded theoretical account of quiet quitting as a situated social phenomenon. Participants were full-time remote employees with a minimum of twelve months’ tenure who self-identified as having deliberately reduced discretionary effort, drawn from technology, consulting, financial services, healthcare IT, publishing, and creative industries. Our analysis reveals three aggregate dimensions: (1) resource depletion through technological demands, (2) disrupted reciprocity in distributed employment relationships, and (3) motivational withdrawal as boundary protection. Each articulated through eleven first-order concepts and five second-order themes. We integrate these findings across four established motivational and relational theories to advance a process model we term Remote Quiet Quitting (RQQ). The model theorises RQQ as a staged, adaptive response to chronic need-thwarting and perceived contract breach, culminating in a ‘minimal viable presence’ strategy. Theoretical contributions, practical implications for HRM practice, and avenues for future research are discussed.